1995
DOI: 10.1021/bi00047a002
|View full text |Cite
|
Sign up to set email alerts
|

Net sugar transport is a multistep process. Evidence for cytosolic sugar binding sites in erythrocytes

Abstract: Human erythrocyte net sugar transport is hypothesized to be rate-limited by reduced cytosolic diffusion of sugars and/or by reversible sugar association with intracellular macromolecules [Naftalin, R.J., Smith, P.M., & Roselaar, S.E. (1985) Biochim. Biophys. Acta 820, 235-249]. The present study examines these hypotheses. Protein-mediated 3-O-methylglucose uptake at 4 degrees C by human erythrocytes and by resealed, hypotonically lysed erythrocytes (ghosts) is inhibited by increasing solvent viscosity. Protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
53
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 40 publications
7
53
0
Order By: Relevance
“…Table 1 summarizes fit parameters for ghosts lacking and containing ATP. Equilibrium exchange time courses have been studied previously by this laboratory, but biphasic transport was observed only at the lowest 3MG concentration employed (0.1 mM) (23), where biphasic exchange may be related to GLUT1 sugar binding. That study did not monitor transport beyond 5 min, which explains why biphasic equilibrium exchange transport at higher 3MG concentrations was not observed.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Table 1 summarizes fit parameters for ghosts lacking and containing ATP. Equilibrium exchange time courses have been studied previously by this laboratory, but biphasic transport was observed only at the lowest 3MG concentration employed (0.1 mM) (23), where biphasic exchange may be related to GLUT1 sugar binding. That study did not monitor transport beyond 5 min, which explains why biphasic equilibrium exchange transport at higher 3MG concentrations was not observed.…”
Section: Resultsmentioning
confidence: 90%
“…Evidence for an unstirred layer comes from three sources. Net 3MG uptake in human red blood cells displays biphasic kinetics, suggesting rapid equilibration with an unstirred layer and slower equilibration with bulk cytosol (23). Steady-state sugar exit in human red blood cells deviates from Michaelis-Menten kinetics at low intracellular sugar concentration in a way that is characteristic of an intracellular unstirred layer (10,28).…”
Section: Discussionmentioning
confidence: 97%
“…The estimated r v for glucose of 0.34 is thus only 17% of the expected ratio and likely represents the size of the intermediate occlusion compartment. Occlusion volume was estimated at 30 -40% of intracellular glucose space in human erythrocytes (6,12) and 35% in cultured bovine mammary epithelial cells (25). Intracellular ATP will influence the size of the occlusion space, possibly through allosteric interaction with the GLUT1 homotetramer.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose serves as a main energy source in chondrocytes (4,5), as a main precursor for glycosaminoglycan synthesis (6, 7), and as a regulator of the cell responses to certain growth factors (44). GLUTs also participate in facilitated transport of glucosamine and N-acetylglucosamine (45,46), which can modify inflammatory responses of chondrocytes (47) and serve as efficient precursors of glycosaminoglycan synthesis (48). Finally, GLUTs (predominantly GLUT1 and GLUT3) facilitate transport of dehydroascorbic acid (49), which induces chondrocyte differentiation (50) and regulates extracellular matrix gene expression, including type II collagen (51).…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that GLUT1 protein has a single N-glycosylation site at Asn 45 , which is heterogeneously glycosylated (25). Glycosylated GLUT1 protein was shown to have a 2-to 2.5-fold lower K m for 2DG binding (62), an increased protein stability, and an increased rate of protein incorporation into the plasma membrane than its nonglycosylated analog (62).…”
Section: Discussionmentioning
confidence: 99%